2013
DOI: 10.1111/ajt.12155
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Established Chronic Lung Allograft Dysfunction Predicts Extracorporeal Photopheresis Response in Lung Transplant Patients

Abstract: Chronic lung allograft dysfunction (CLAD) remains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 42 publications
5
67
1
1
Order By: Relevance
“…[17,18] Although clinical investigations of ECP for HCT-BOS are fairly limited, a more substantial experience with ECP has been reported for LTX-BOS. [3,19] These studies have shown a significant lessening of FEV1 decline, and Greer et al [19] found significantly improved progression-free survival in a LTX recipient cohort that had been refractory to firstline therapy with AZI, and subgroup analysis showed that patients with BAL neutrophilia were more likely to respond to ECP.…”
Section: How Can Bos Be Treated?mentioning
confidence: 99%
“…[17,18] Although clinical investigations of ECP for HCT-BOS are fairly limited, a more substantial experience with ECP has been reported for LTX-BOS. [3,19] These studies have shown a significant lessening of FEV1 decline, and Greer et al [19] found significantly improved progression-free survival in a LTX recipient cohort that had been refractory to firstline therapy with AZI, and subgroup analysis showed that patients with BAL neutrophilia were more likely to respond to ECP.…”
Section: How Can Bos Be Treated?mentioning
confidence: 99%
“…Macrolide treatment does not seem to affect these patients (40). However extracorporeal photopheresis (ECP), a leukapheresis-based procedure, was beneficial (41), and seems to be mainly an adequate treatment for patient with macrolide resistant airway neutrophilia (42). Part of this beneficial effect can be explained by effects of ECP on reducing inflammatory cytokines, chemokines and donor specific antibodies (43).…”
Section: Treatmentmentioning
confidence: 99%
“…Nevertheless, no large cohorts have been described so far and therefore more evidence is needed before antifibrotics can be introduced in general clinical practice. ECP therapy does not seem to be able to slow down rCLAD progression and therefore does not seem a viable option (42). Another drug with potential to slow down disease progression is alemtuzumab (Campath-1H), an antagonist of CD52 which is expressed on B-cells, lymphocytes, dendritic cells and monocytes.…”
Section: Treatmentmentioning
confidence: 99%
“…Of interest, differences between responders to ECP therapy as compared to non-responders included time of onset of BOS (early posttransplant development of BOS), kinetics of lung functional decline (slower decrease of lung function at the beginning of BOS) and BOS severity (lower BOS grade). A study by the Hannover group investigated the effects of ECP on different phenotypes of CLAD suggesting that patients with restrictive allograft syndrome (RAS), for example, respond less to ECP than patients with neutrophilic CLAD (47). Conversely, a recent study performed by Del Fante et al (48) reported a 10 years follow-up of 48 CLAD patients treated with ECP, and in these patients, no association between FEV 1 decline pattern and failure of ECP therapy or CLAD phenotype was found.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%